Phytoseiid mites of the subfamily Phytoseiinae (Acari: Phytoseiidae) from sub-Saharan Africa - Ueckermann, E.A.; Zannou, I.D.; Moraes, G.J. de; Oliveira, A.R.; Hanna, R.; Yaninek, John S. (2007)
This is the seventh publication in a series concerning the phytoseiid mites of sub-Saharan Africa. Sixteen phytoseiid species of the subfamily Phytoseiinae (Chantia: 1 species, Phytoseius: 13 species and Platyseiella: 2 species) are reported in this paper. They include all species of this subfamily known to occur in sub-Saharan Africa. Ten of these species are redescribed. Most of those species were collected in cassava habitats in tropical Africa and in other habitats in South Africa. A key is included to help in the separation of these species.